BAHASA KIASAN PADA KUMPULAN PUISI “CINTA DAN KISAH-KISAH YANG SULIT SELESAI” - Izzati El Milla Milla; Dzarna Dzarna; Yerry Mijianti Mijianti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
This research was intended to explain the figurative language on the collection of poems entitled Cinta dan Kisah-kisah yang Sulit written by Gita Romadhona. The figurative languages in group of poem described the feeling of the writer and used the aesthetics and meaningful figurative languages. This research was qualitative descriptive. The research data were in the form of dictions, phrases, and lyrics that showed figurative language. The resource of the data was the collection of poems entitled Cinta dan Kisah-kisah yang Sulit written by Gita Romadhona. The instruments of the data were the researcher herself and supported by the table of the data collection. The technique of the data collection was reading and marking the data that contained figurative language on the collection of poems that has been researched. The analysing data included continuously reading, collecting the data, coding, describing the data and writing the conclusion. The testing technique of the data validity was the enhancement diligence technique. Based on the results of the research, it was found about simile figurative languages, personifications, allegories, cynics, epics, metonymies, and metaphors. The figurative languages used were the expressions of the writer itself.